Distance Learning in Museums: A Review of the Literature - Ennes, Megan; Lee, Imani N. (International Review of Research in Open and Distributed Learning, 2021)
Distance learning has become an important tool in many fields of education. Museums, like other educational institutions, have been offering distance learning programs to their audiences for more than 30 years. This scoping study examined the published literature related to distance learning programs in museums to inform future research in this field. Searches were conducted in three academic databases in addition to journal hand searches. This resulted in 954 unique citations associated with distance learning in museums. Of these, 17 articles met the criteria for inclusion in the study. Forwards and backwards searches resulted in the addition of two books. A search of the research hosted by the Center for Advancement of Informal Science Education resulted in one additional study for a total of 20 manuscripts. Upon analysis, four major themes were identified. These included benefits and barriers related to distance learning programs in museums, partnerships, and educators’ changing roles as they relate to distance learning programs. Each of these themes is described and areas for future research are identified. Future work should move beyond the predominately evaluative case studies and pursue larger questions about how future research might support museums as they continue to design and implement online programming. This may include exploring best practices in museum-based distance learning and how to develop effective professional development opportunities for the educators engaged in these programs. Such research will enhance museum-based distance learning programs so that they can continue to support global learners.